The conversion of forests to agricultural croplands significantly depletes soil organic carbon reserves, total nitrogen, and available potassium, reaching critical thresholds in the Peruvian Amazon - Solórzano-Acosta, Richard; Cruz-Luis, Juancarlos; Chuchon-Remon, Rodolfo; Romero-Chávez, Lorena Estefani; Lozano, Andi; Gaona-Jimenez, Nery; Vallejos-Torres, Geomar (Frontiers in Soil Science, 2025)
IntroductionLand-use change from primary forests to agricultural croplands can degrade soil quality by depleting soil organic carbon (SOC), total nitrogen (STN), and soil-available potassium (SAK). The magnitudes and thresholds of these losses in the Peruvian Amazon remain insufficiently quantified.MethodsWe assessed six land-use systems—two primary forests and four croplands (coffee, cocoa, oil palm, camu camu)—collecting 72 surface soil samples (0–20 cm) from 12 subplots per system using pit sampling. SOC, STN, and SAK were measured with standard laboratory procedures and compared across land uses.ResultsThe humid primary forest (WE–PF) had the highest nutrient status (SOC 118.99 t C ha⁻¹; STN 0.35%; SAK 181.83 mg kg⁻¹). The lowest values occurred in croplands, especially camu camu (SOC 23.93 t C ha⁻¹; STN 0.08%). Forest-to-cropland conversion was associated with average reductions of 58.98% (SOC), 59.49% (STN), and 59.66% (SAK). Among crops, coffee showed the smallest deficit (18.04%), whereas camu camu showed the largest SOC deficit (30.92%).DiscussionConverting forests to croplands critically depletes SOC, STN, and SAK, indicating substantial nutrient losses and concomitant deterioration of soil quality. These findings support conserving primary forests and promoting agroforestry and soil-restorative practices to mitigate degradation in the Peruvian Amazon.